Supplementing calcium salts of soybean oil to beef steers early in life to enhance carcass development and quality. (20th August 2019) - Schubach, Kelsey M; Cooke, Reinaldo F; Brandão, Alice P; de Sousa, Osvaldo A; Schumaher, Thiago F; Jump, Donald B; Pohler, Ky G; Bohnert, David W; Marques, Rodrigo S
Abstract: This study evaluated the effects of supplementing Ca salts of soybean oil (CSSO ) to beef steers at 2 mo of age via creep-feeding, and/or during a 40-d preconditioning period on performance and carcass development responses. A total of 64 steers were enrolled in this study over 2 yr (32 steers per year), with 4 periods each year: creep-feeding (CF ; day 0 to 60), preweaning (day 61 to weaning on day 124 and 127 of year 1 and 2, respectively), preconditioning (PC ; day 132 to 172 in year 1 and day 135 to 175 of year 2), and feedlot (feedlot arrival to slaughter, day 173 to 378 in year 1 and day 176 to 385 in year 2). On day 0 steers were ranked by body weight (BW ) and age (114 ± 4 kg of BW; 66.1 ± 0.9 d of age) and allocated to 1 of 16 pens. Pens were randomly assigned to receive CSSO during CF (80 g/d per steer) and/or PC (150 g/d per steer) in a 2 × 2 factorial arrangement of treatments. During CF and PC, nonsupplemented steers (CON ) were provided an isolipidic prilled saturated fat supplement. Steer BW was recorded on day 0, 60, at weaning, and prior to feedlot shipping. Carcass traits were recorded upon slaughter. On day 0, 60, at weaning, prior to feedlot shipping, and during the feedlot period, blood samples were collected and longissimus muscle (LM ) biopsies were collected. On day 60, steers that received CSSO during CF had greater ( P < 0.01) plasma concentrations of linoleic and ω-6 compared with CON (CF treatment × day; P ≤ 0.05). Steers that received CSSO during PC had greater ( P < 0.01) plasma concentrations of linoleic, ω-6, and total fatty acids compared with CON at feedlot shipping (PC treatment × day; P ≤ 0.05). A PC treatment × day interaction was also detected ( P = 0.04) for mRNA expression of peroxisome proliferator-activated receptor gamma (PPAR-γ ), which was greater ( P = 0.04) at feedlot shipping for steers receiving CSSO during PC. Interactions between CF treatment × day were detected ( P ≤ 0.01) for mRNA expression of adipocyte fatty acid-binding protein, fatty acid synthase, PPAR-γ, and stearoyl-CoA desaturase, which were greater ( P ≤ 0.02) in the feedlot in steers receiving CSSO during CF. No treatment differences were detected for ( P ≥ 0.18) performance or carcass traits, including marbling and backfat thickness. Results from this study suggest that supplementing CSSO to suckled beef steers via creep-feeding upregulated mRNA expression of the adipogenic genes investigated herein later in life. These outcomes, however, were not translated into improved carcass quality.